Latin American Melodrama: Passion, Pathos and Entertainment - Tompkins, Cynthia (Imagofagia, 2021)
Sobre Sadlier, Darlene J. (ed.). Latin American Melodrama: Passion, Pathos and Entertainment. Urbana, University of Illinois Press, 2009, 200 pp., ISBN: 978-0252076558. Palabras claves: reseña, Darlene J. Sadlier, Latin American Melodrama: Passion, Pathos and Entertainment.